Relatório de Estágio Profissional "O caminho até ao topo da montanha: A relação pedagógica do professor-aluno como fator de sucesso educativo" - Alberto Miguel Arantes Senra (2019)
The Professional Internship is part of the 2nd year of the Master´s Degree in Physical Education Teaching in Primary and Secondary Education in the Sports School of the University of Porto. The aim is to provide the first contact with labor market, specifically the education situation in schools (Batista et al., 2012), being conducted with Guiding College Professor and School Cooperative Professor. This document reports results obtained during the first contact, that is, address the teacher evolution process. It is organized in 5 chapters which will be address. The first chapter, "Introduction", exposes the purpose of this document. The second "Biographical framework", addresses anticipatory socialization, sports experiences, internship expectations and the reason that lead to this professional career choice. The third chapter, "Professional Practice Framework", refers to the various aspects of professional training: institutional, legal and functional. "Professional Practice of Realization", the fourth chapter, includes three areas that includes information on the preparation, performance and evaluation of teaching, as well, description of the different developed school activities. The penultimate area integrates an study action-research, where, through the implementation of the Sports Education Model, it was intended to develop motivation to conduct Physical Education and/or leisure activities. As for the last chapter, "Conclusions and perspectives for the Future", there is the final reflection of the internship year, with an assessment of the achievement of goals, perceptions about personal and professional evolution and aspirations for the future. In short, it resulted in a set of experiences that allowed to develop knowledge and competences essential for development as professional and personal that made it possible to prepare for life as a teacher.